Dinamika Studi Hadis di PP Hasyim Asyari Tebuireng Jombang: Dari Klasikal Hingga Mahad Aly - Suryadilaga, Muhammad Alfatih (AL QUDS : Jurnal Studi Alquran dan Hadis, 2019)
The study of hadith in pesantren continues to develop along with the development of time and dynamics in it. At least seen in the curriculum both at the level of MTs., MA and Ma’had ly Aly PP Hasyim Asyari Tebuireng Jombang as one of the equivalent undergraduate education. The tradition of reading hadith both by way of bandongan and sorogan becomes classical at the madrasa level both at the MA and MTs levels. as well as a variety of studies and book readings that were studied both in the month of Ramadan and others. The study of hadith is increasing and deeper in the tradition of Mahad Aly. The study of Hadith in it has various hadith books with a focus on the books of the hadith that are not patient. This is different from the tradition of reading the hadith at the lower level. In general, the popular hadith books among Islamic boarding schools are Bulugh al-Maram and Riyadush Shalihin. The study of the hadith continues to grow with a variety of studies not only in the books of the traditions that contain the traditions but also the books of the science of traditions, books both sahih Bukhari or other hadith books with a variety of sanad in them and the books of hadith. Thus, the study of hadith in Ma’had Aly is more diverse because with mahasantri prepared to become scholars who tafaqquh fi al-din. So that this study makes the study of hadith books in pesantren very diverse along with the birth of strata one that is typical of pesantren